Chlamydia pneumoniae and Mycoplasma pneumoniae in children with cystic fibrosis: impact on bacterial respiratory microbiota diversity. Issue 1 (28th November 2020) - Pittet, Laure F; Bertelli, Claire; Scherz, Valentin; Rochat, Isabelle; Mardegan, Chiara; Brouillet, René; Jaton, Katia; Mornand, Anne; Kaiser, Laurent; Posfay-Barbe, Klara; Asner, Sandra A; Greub, Gilbert
ABSTRACT: Objectives: The contribution of intracellular and fastidious bacteria in Cystic fibrosis (CF) pulmonary exacerbations, and progressive lung function decline remains unknown. This project aimed to explore their impact on bacterial microbiota diversity over time in CF children. Methods: Sixty-one children enrolled in the MUCOVIB multicentre prospective cohort provided 746 samples, mostly nasopharyngeal swabs, throat swabs and sputa which were analysed using culture, specific real-time qPCRs and 16S rRNA amplicon metagenomics. Results:   Chlamydia pneumoniae ( n  = 3) and Mycoplasma pneumoniae ( n  = 1) were prospectively documented in 6.6% of CF children. Microbiota alpha-diversity in children with a documented C. pneumoniae was highly variable, similarly to children infected with Staphylococcus aureus or Pseudomonas aeruginosa . The transition from routine follow-up visits to pulmonary exacerbation ( n  = 17) yielded variable changes in diversity indexes with some extreme loss of diversity. Conclusions: The high rate of C. pneumoniae detection supports the need for regular screenings in CF patients. A minor impact of C. pneumoniae on the microbial community structure was documented. Although detected in a single patient, M. pneumoniae should also be considered as a possible aetiology of lung infection in CF subjects. Abstract : This study documented Chlamydia pneumoniae in 4.9% of children with cystic fibrosis, stressing the need for routine screening, and investigated its impact on airway microbiota by 16S amplicon-based metagenomics.